A Comparison of the Concept of Romantic Love in the Novels Ayat-ayat Cinta 2 and Salju Sakinah: (Perbandingan Konsep Cinta Romantisme dalam Novel Ayat-ayat Cinta 2 dan Salju Sakinah) (Malay Literature, 2018)
This study uses textual analysis to explore the concept of romantic love by comparing the Indonesian Islamic novel, Ayat-Ayat Cinta 2, by Habiburrahman El-Shirazy with the Malaysian Islamic novel, Salju Sakinah, by Zaid Akhtar. This investigation utilises the theory of persuratan baru (genuine literature) by focusing on the concept of the nature and function of literature. This study discovers that the creation of novels infused with Islamic elements and romantic love in Indonesia and Malaysia is influenced by two main factors, which are the awareness of the writer to disseminate Islamic messages and the profit motive of the publisher. These two factors cause novels, imbued with Islamic elements and romantic love, to become a branded or marketable commodity in both countries. The findings reveal that Ayat-Ayat Cinta 2 utilises the concept of romantic love with emphasis on sexual intimacy while Salju Sakinah places emphasis on the language of understanding over physical intimacy.Keywords: Islamic novels, Ayat-Ayat Cinta 2, Salju Sakinah, romantic love, sexuality.